Hahn-Steinthal fracture: report of two cases - Pogliacomi, F.; Concari, G.; Vaienti, E. (Acta Biomedica Atenei Parmensis, 2005)
Isolated capitellar fractures are rare injuries accounting for only 1% of all elbow fractures. Type I or Hahn-Steinthal fractures require internal fixation to restore the anatomic integrity of the elbow joint. Many different fixation methods have been described and, independently of the method chosen, precise reduction is mandatory to maximize articular congruency and to diminish the potential for secondary osteoarthritis. The treatment and the outcome of two type I capitellar fractures are described in this study. One patient (April 1999) underwent open reduction and Kirschner wire fixation while the second patient (May 2004) underwent open reduction and Acutrak standard screw fixation. In both patients no complications occurred and normal elbow function was recovered. No signs of avascular necrosis (AVN), heterotopic ossifications and degenerative osteoarthritis were detected.We conclude that Acutrak screw fixation is a reliable method of treatment because it enables a good interfragmentary compression, earlier mobilization, faster functional elbow recovery, and metal work removal is rarely necessary.